A PUBS Case in a Palliative Care Unit Experience - M. R. Restuccia; M. Blasi (Case Reports in Oncological Medicine)
Purple urine bag syndrome (PUBS) is a rare condition in which purple discoloration of the collecting bag and its associated tubing occurs. It is considered a benign condition. PUBS is usually associated with urinary tract infection occurring in elderly bedridden women, with chronic urinary catheterization. This syndrome is usually reported to occur in alkaline urine, but here we describe a rare case of PUBS involving acidic urine.